2023
DOI: 10.3892/etm.2023.11927
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogressive disease after immune checkpoint inhibitor therapy in a patient with non‑small cell lung cancer who harbors a TGFBR2 mutation: A case report

Abstract: We previously demonstrated that a transforming growth factor β type II receptor (TGFBR2) mutation can predict resistance to immune checkpoint inhibitors (ICIs) in patients with advanced non-small cell lung cancer (NSCLC), based on publicly available immunotherapeutic cohorts. However, the efficacy of ICI-based regimens in patients with advanced NSCLC harboring TGFBR2 mutations in the real-world setting is rarely reported. The present study describes the case of a patient with advanced NSCLC who harbors a TGFBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Subsequently, we also reported a case in which a lung cancer patient with a TGFBR2 mutation experienced hyper‐progression after receiving ICI monotherapy. 10 These findings suggest that the biomarkers discovered by IMPACT may be validated in the clinic, which shows the potential value of IMPACT in biomarker exploration.…”
mentioning
confidence: 83%
“…Subsequently, we also reported a case in which a lung cancer patient with a TGFBR2 mutation experienced hyper‐progression after receiving ICI monotherapy. 10 These findings suggest that the biomarkers discovered by IMPACT may be validated in the clinic, which shows the potential value of IMPACT in biomarker exploration.…”
mentioning
confidence: 83%
“…It has been reported that HPD occurs more frequently in patients receiving monotherapy with PD-1 and PD-L1 inhibitors compared to those treated with immunotherapy combined with chemotherapy in NSCLC (17.6% vs. 2.9%, p=0.031) (23). Furthermore, it has been suggested that combining chemotherapy and immunotherapy may be effective in preventing HPD as chemotherapy may synergize with immunotherapy to enhance the anti-tumor effect (24,25). Two factors were found to be associated with HPD.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%